The Impact of School Program Strategies on Student Character Development In The Era of Educational Transformation - Rusnan Hadi; Muhammad Thoriq Bin Ziyad; A. Farmozi Zain; Lalu Sumardi; Dadi Setiadi (Yayasan Cendekia Gagayunan Indonesia, 2026)
The rapid advancement of digital technologies has reshaped educational ecosystems and compelled schools to adopt learning paradigms that integrate character formation as a central dimension of 21st-century competency development. This study investigates the impact of school program strategies on students’ character development within the dynamic context of digital-era educational transformation. Employing a qualitative case study design, the research was conducted in several Indonesian secondary schools that have implemented digitally supported and collaborative character education initiatives. Data were collected through in-depth interviews, participatory observations, and the analysis of school policy documents, followed by triangulation to ensure methodological rigor. The findings reveal that school program strategies explicitly grounded in character values such as discipline, responsibility, empathy, and collaboration exert a significant influence on students’ behavioral patterns and socio-emotional dispositions. Technology integrated initiatives, including online learning platforms and digital extracurricular activities, enhance the internalization of character values by creating contextual and meaningful learning experiences. Nonetheless, challenges persist, particularly regarding inconsistencies in implementation and varying levels of engagement from teachers and other stakeholders. Overall, the study underscores the importance of strong alignment between school policies, instructional practices, and the broader learning environment to cultivate students who are adaptive, ethically minded, and socially responsible in the digital transformation era.